Early hemodynamic predictors of good outcome and reperfusion injury after endovascular treatment. (11th June 2019) - Baracchini, Claudio; Farina, Filippo; Palmieri, Anna; Kulyk, Caterina; Pieroni, Alessio; Viaro, Federica; Cester, Giacomo; Causin, Francesco; Manara, Renzo
Abstract : Objective: To find early hemodynamic predictors of outcome and reperfusion injury in patients with acute ischemic stroke due to anterior circulation large artery occlusion (LAO) after endovascular treatment (EVT). Methods: Serial transcranial color-coded sonography examinations assessed the vessel status and cerebral hemodynamics of 185 (109 [58.9%] men, mean age 69.5 ± 12.3 years) consecutive patients with acute anterior circulation LAO soon after, at 48 hours after, and 1 week after EVT. Results: Successful recanalization (odds ratio [OR] 0.25, 95% confidence interval [CI] 0.11–0.61) and normal peak systolic velocity (PSV) ratio (PSV of recanalized middle cerebral artery/PSV of contralateral middle cerebral artery) at 48 hours (OR 0.22, 95% CI 0.15–0.64) and after 1 week (OR 0.11, 95% CI 0.07–0.31) from EVT were independent predictors of good outcome at 3 months. Thrombectomy failure (OR 10.22, 95% CI 1.47–45.53) and pathologic PSV ratio at 1 week from EVT (OR 15.23, 95% CI 4.54–46.72) were associated with a worse 90-day outcome. Patients who subsequently developed postinterventional intracranial hemorrhage (ICH) showed a higher mean PSV ratio (3.5 ± 0.2 vs 2.4 ± 0.1, p < 0.0001) soon after successful recanalization. In multivariate analysis, early PSV ratio was independently associated with postprocedural ICH (OR 8.474, 95% CI 3.066–45.122, p < 0.01]. At 1 week from EVT, 15 of 21 (71.4%) patients with ICH who resumed normal PSV values had a better 90-day outcome (modified Rankin Scale score 0–2: 40% vs 0%). Conclusion: Post-EVT ultrasound monitoring of stroke patients might be an effective bedside method for assessing treatment efficacy, shedding light on outcome variability and identifying patients at increased risk of ICH.